EXPERIMENTAL EVALUATION OF CARRIER FREQUENCY OFFSET TRACKING PERFORMANCE IN SINGLE CARRIER WiMAX (IEEE 802.16-2004) RADIO - Ilkhan, Mehmet Akif; Canbolat, Ahmet Ihsan; Ozen, Ali (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2011)
Simulation and experimental carrier frequency offset (CFO) tracking performances of conventional adaptive equalization algorithms have been evaluated in real-time WiMAX (IEEE 802.16-2004) radio channels in this paper. Instead of using a certain type of channel profile this study concentrates on true frequency selective Rayleigh fading channels in WiMAX radio environment around 3.5 GHz. Bit Error Rate (BER) performances of the most commonly used conventional equalization techniques; Least Mean Squares Decision Feedback Equalizer (LMS-DFE) and Recursive Least Squares DFE (RLS-DFE) algorithms are investigated in study. The simulation results have demonstrated that the simulation and experimental performances are compatible with each other and extremely satisfying.
Keywords: Experimental BER; adaptive equalization; WiMAX (IEEE 802.16-2004); CFO; LMS-DFE; RLS-DFE.; Engineering